Climate change and the indoor environment : impacts and adaptation. (CIBSE ;, 2005)
There is compelling scientific evidence that our climate is changing, and it is probable that average temperatures will increase by several degrees over the coming century. These increases in temperature are expected to have a major impact on the indoor environment of buildings in the UK. This publication addresses several questions through dynamic thermal computer modelling of 13 case study buildings, chosen to provide a cross section of UK building types, including dwellings, schools and offices, and illustrate a range of different approaches to comfort cooling provision. --